If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(x + 2) = 297 Reorder the terms: 3x(2 + x) = 297 (2 * 3x + x * 3x) = 297 (6x + 3x2) = 297 Solving 6x + 3x2 = 297 Solving for variable 'x'. Reorder the terms: -297 + 6x + 3x2 = 297 + -297 Combine like terms: 297 + -297 = 0 -297 + 6x + 3x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-99 + 2x + x2) = 0 Factor a trinomial. 3((-11 + -1x)(9 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-11 + -1x)' equal to zero and attempt to solve: Simplifying -11 + -1x = 0 Solving -11 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -1x = 0 + 11 Combine like terms: -11 + 11 = 0 0 + -1x = 0 + 11 -1x = 0 + 11 Combine like terms: 0 + 11 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11Subproblem 2
Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9Solution
x = {-11, 9}
| 2+z^2+3z=0 | | 6x+4/3=5 | | 2(6x+4)=5 | | x+2y-z=-7 | | 25x-1=5x-1-100 | | 2n^2-16n+30=0 | | 16z-51=45+16z | | 66-34z=41-34z | | C(x)=9x+5000 | | 2xy=32 | | -3(y+3)+5= | | 2x=3x+4x | | -b(a^10-ab+b^10)= | | -4w^2+8w-3=0 | | f(x)=-7x^2+7x+8 | | 88/x=12 | | f(x)=-9x^2+3x+5 | | f(x)=-3x^2+4x+3 | | 5-a=a | | -4v^2+20v-21=0 | | 5m+12=18 | | 4x+6=2x+40 | | 2y-36=-5y | | x(6-x)=0 | | a+46=3a | | X/3=10/7 | | 2w^2-15w+18=0 | | 5v^2-34v-24=0 | | 5v^2-44v-24=0 | | -3/5-6/7= | | 2.42+(-8.47)= | | z^4=121 |